Scientific and technical acronyms, symbols, and abbreviations - Erb, Uwe (John Wiley & Sons, 2001)
Scientific and Technical Acronyms, Symbols, and Abbreviations is the most comprehensive reference of its type, covering more scientific and technical disciplines than any other available book. This invaluable resource will help scientists, engineers, and researchers understand and utilize current terminology in almost any field-from aeronautics to zoology.